WIPO Technology Trends 2019 : Artificial Intelligence. - Organization, World Intellectual Property (World Intellectual Property Organization, 2019)
This report is the first in a new series from WIPO tracking the development of technologies through the analysis of data on innovation activities. It reveals trends in patenting of artificial intelligence (AI) innovations, the top players in AI from industry and academia, and the geographical distribution of AI-related patent protection and scientific publications. Its findings are accompanied throughout by commentary and industry perspectives from more than 20 of the world's leading experts in AI, making it of particular interest to business leaders, researchers and policymakers.